Which factors are associated with the prevalence of meniscal repair? - Song, Xiaoxiao (BMC Musculoskelet Disord, 2021)
ABSTRACT: Purpose To investigate the potential factors associated with the prevalence of meniscal repair Methods Patients who received partial meniscectomy or meniscal repair in our institution from Jan 2015 to Dec 2019 were included in current study. The inclusion criteria were (1) meniscus tear treated using meniscectomy or repair, (2) with or without concomitant anterior cruciate ligament reconstruction, (3) not multiligamentous injury. Demographic data, including sex, age, body mass index (BMI), injury-to-surgery interval and intra-articular factors such as the location of injury, medial or lateral, ACL rupture or not and the option of procedure (partial meniscectomy or repair) were documented from medical records. Univariate analysis consisted of chi-square. Multivariate logistic regression was then performed to adjust for confounding factors. Results 592 patients including 399 males and 193 females with a mean age of 28.7 years (range from 10 to 75 years) were included in current study. In the univariate analysis, male (p = 0.002), patients aged 40 years or younger (p < 0.001), increased weight (p = 0.010), Posterior meniscus torn (0.011), concurrent ACL ruputure (p < 0.001), lateral meniscus (p = 0.039) and early surgery (p < 0.001) were all associated with the prevalence of meniscal repair. However, After adjusting for confounding factors, we found that age (OR, 0.35; 95% CI, 0.17 - 0.68, p = 0.002), ACL injury (OR, 3.76; 95% CI, 1.97 – 7.21, p < 0.001), side of menisci (OR, 3.29; 95% CI, 1.43 – 7.55, p = 0.005), site of tear (OR, 0.15; 95% CI, 0.07 – 0.32, p < 0.001), and duration of injury (OR, 0.46; 95% CI, 0.28 – 0.82, p = 0.008) were associated with the prevalence of meniscus repair. Conclusions Meniscal tear in aged patients especially those with concomitant ACL injury is likely to be repaired. Additionally, in order to increase the prevalence of repair and slow down progression of OA, the surgical procedure should be performed within two weeks after meniscus tear especially when the tear is located at lateral meniscal posterior. STUDY DESIGN: Case-control study; level of evidence, 3.